Analyzing The Transitivity Process of Descriptive Texts in Sixth Grade Elementary’s LKS - Dewi, Adinda Purnama; Samsi, Yogi Setia; Miftkah, Fauzi; Dewi, Indah Purnama (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research presents a study analyzing the transitivity process of several descriptive texts in the English textbook or Lembar Kerja Siswa (LKS) for sixth-grade elementary school. Few researches have focused on the transitivity process in students' writing, while the transitivity process has been identified in textbooks in this research. The purpose of this research is to investigate how transitivity process are used in textbook (LKS) and to identify the most frequently used. This research analyzed eight textbook descriptive texts using a descriptive quantitative method. To analyze the data, the researcher used Halliday's systemic functional grammar theory of transitivity. The analysis revealed that there were only four transitivity process that appeared in the textbook, there were relational process (42.23%), material process (32.31%), existential process (15.38%), and mental process (1.54%), also behavioral process and verbal process did not appear. This shows relational process used in descriptive text to describe function. Material process also used in descriptive text to give physical movement.